Excavations at the Settlement of Artyushchenko–I (Bugazskoe) on the Taman Peninsula - Vinogradov, Yurij A. (Hyperboreus, 2015)
A survey of the excavations at the settlement of Artyushchenko I (Bugazkoe) conducted by the Bosporan expedition of the Institute for the History of Material Culture, RAS.